1995
DOI: 10.4098/at.arch.95-47
|View full text |Cite
|
Sign up to set email alerts
|

B chromosomes in the wood mice (genus Apodemus )

Abstract: Spatial and temporal distribution of supernumerary or B chromosomes were studied in natural populations of wood mice. A total of 859 individuals belonging to several species from Eurasia were examined. A very high percentage of individuals possessing B chromosomes was found in Apodemus peninsulae (97.9%, n = 47), a high percentage in A. flavicollis (42.5%, n = 362), and a low one in A. sylvaticus (2.4%, n = 210). No B chromosomes were observed in A. uralensis (n = 10), A. fuluipectus (n = 19), A. hermonensis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 27 publications
1
30
1
Order By: Relevance
“…In the Russian Far East, variation in the number of Bs is limited to 6 and dot-like Bs are not present (Kral, 1971;Kartavseva et al, 1988) indicating that this species has a locality-dependent B chromosome system. Contrary to such high frequencies of Bs in A. peninsulae and A. flavicollis, Zima and Macholá n (1995) found that the frequency of A. sylvaticus individuals with Bs is very low (2.4 %). Kartavtseva (1994) also found that such sporadic occurrence of Bs is characteristic for the striped field mouse, Apodemus agrarius.…”
Section: Frequency Of B Chromosomesmentioning
confidence: 42%
See 1 more Smart Citation
“…In the Russian Far East, variation in the number of Bs is limited to 6 and dot-like Bs are not present (Kral, 1971;Kartavseva et al, 1988) indicating that this species has a locality-dependent B chromosome system. Contrary to such high frequencies of Bs in A. peninsulae and A. flavicollis, Zima and Macholá n (1995) found that the frequency of A. sylvaticus individuals with Bs is very low (2.4 %). Kartavtseva (1994) also found that such sporadic occurrence of Bs is characteristic for the striped field mouse, Apodemus agrarius.…”
Section: Frequency Of B Chromosomesmentioning
confidence: 42%
“…in a peripheral area with unfavorable conditions. Much higher frequencies of animals with Bs were found in populations of Apodemus peninsulae (95.6 and 97.8 % respectively) by Volobujev (1981) and Zima and Macholá n (1995). In many populations in the Russian Far East all animals possess Bs (Kartavtseva et al, 2000).…”
Section: Frequency Of B Chromosomesmentioning
confidence: 91%
“…Molecular markers that are unique to the DNA of Bs were demonstrated in this species (Tanic et al, 2000). Substantial differences in the frequencies of B carriers were observed between different populations (Vujošević et al, 1991;Vujošević and Blagojević, 1994;Zima and Macholán, 1995). In this species, constant, apparently equilibrium frequencies of Bs were observed in the course of 8-year studies, notwithstanding the changes in population density (Vujošević, 1992;and unpublished data).…”
Section: Introductionmentioning
confidence: 73%
“…The effects of their presence on population biology are not understood (Vujošević, 1993). Bs are common in the yellow-necked mouse, Apodemus flavicollis (Soldatovic et al, 1975;Kral et al, 1979;Giagia et al, 1985;Sablina et al, 1985;Vujošević et al, 1991;Nadjafova et al, 1993;Boeskorov et al, 1995 andMacholán, 1995). Molecular markers that are unique to the DNA of Bs were demonstrated in this species (Tanic et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the populations of yellow-necked mice, Apodemus flavicollis, B chromosomes are widespread (Zima & Macholán 1995;Kartavtseva 2002). Accumulated data on the correlation between frequency of Bs and environmental variables in A. flavicollis, as well as those for phenotypic variation, indicate that Bs exert their effects at the level of populations (Vujošević & Blagojević 2000) and it is suggested that, at least in certain environments, the presence of Bs could be beneficial for their host (Zima et al 2003).…”
Section: Introductionmentioning
confidence: 99%